2022
DOI: 10.3390/jcm11164768
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Outcomes and Reinterventions Following Fenestrated/Branched Endovascular Aortic Repair in Post-Dissection and Complex Degenerative Abdominal and Thoraco-Abdominal Aortic Aneurysms

Abstract: Background: The outcome of FBEVAR in post-dissection thoracoabdominal aortic aneurysms has not been well established in the literature. The aim of this study was to compare midterm outcomes following FBEVAR in post-dissection aneurysms to degenerative aneurysms. (2) Methods: This was a retrospective review of all patients undergoing FBEVAR in a single center between 2017 and 2020. The baseline characteristics, intraoperative details, and postoperative outcomes of patients with post-dissection aneurysms were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Of these, 203 were excluded for one or more of the following reasons: provided data on aortic arch disease (n = 21); reported on open or hybrid repair (n = 17); provided data on Mesh Stent (n = 1); case reports, technical notes or case series with >10 patients (n = 18); editorial and review articles (n = 6); provided mixed data on TAAs and TAAAs (n = 14); provided mixed data on degenerative TAAAs and PDTAAAs (n = 51); were irrelevant (n = 61); and/or reported on overlapping patient populations (n = 14) (Figure 1). Finally, 10 studies [32][33][34][35][36][37][38][39][40][41], with a total of 585 patients (1255.65 p-ys), were deemed eligible for inclusion in the meta-analysis (Table 1) (Figure 1). CMD: custom-made device; PMSG: physician-modified stent graft.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 203 were excluded for one or more of the following reasons: provided data on aortic arch disease (n = 21); reported on open or hybrid repair (n = 17); provided data on Mesh Stent (n = 1); case reports, technical notes or case series with >10 patients (n = 18); editorial and review articles (n = 6); provided mixed data on TAAs and TAAAs (n = 14); provided mixed data on degenerative TAAAs and PDTAAAs (n = 51); were irrelevant (n = 61); and/or reported on overlapping patient populations (n = 14) (Figure 1). Finally, 10 studies [32][33][34][35][36][37][38][39][40][41], with a total of 585 patients (1255.65 p-ys), were deemed eligible for inclusion in the meta-analysis (Table 1) (Figure 1). CMD: custom-made device; PMSG: physician-modified stent graft.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding target vessels (TVs), data were provided in eight studies [32][33][34][35][37][38][39][40], with a total of 1815 vessels being incorporated in the repairs with either a fenestration, branch or a scallop. Four studies [33][34][35]40] describing 143 patients with 521 TVs reported a rate of need for perforation of the dissection flap of 3.6% (19/521).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations